ISOLASI, IDENTIFIKASI DAN ENUMERASI BAKTERI Salmonella spp. PADA HASIL PERIKANAN SERTA RESISTENSINYA TERHADAP ANTIBIOTIK - Aulia, Rizky; Handayani, Tri; Yennie, Yusma (Bioma, 2015)
ABSTRACT Salmonella spp. is one of the bacteria that can contaminate fresh fishery products. Diseases that can be caused by the bacteria Salmonella spp. called salmonellosis. Salmonellosis disease can be treated with antibiotics. However, the use of antibiotics continually raises the emergence strains of Salmonella bacteria that are resistant to antibiotics. This study aims to determine the prevalence and number of bacteria Salmonella spp. on fishery products as well as the resistance of Salmonella spp. to antibiotics in Jakarta and Bogor. The number of samples fresh fishery products obtained by 45 samples consisting of: a) 25 samples derived from traditional markets, and b) 20 samples derived from modern market. Isolation performed with conventional method. Identification of Salmonella spp. used biochemical and serological test. Resistance of Salmonella to antibiotics testing using disc diffusion method. The results of the identification Salmonella spp. positive sample traditional market fresh fish as much as 9 samples (36%), whereas the modern market by 6 positive samples contaminated with Salmonella spp. (30%). The number of bacteria Salmonella spp. from traditional market is about: 3,0×100 – 1,1×103 APM/g; from modern market: 3,0×100 – 2,9×102 APM/g. Based on resistance testing of Salmonella spp. to antibiotics, this bacteria has the highest level of resistance to the antibiotic erythromycin types of 93.75%. Keywords: Salmonella spp., fishery, enumeration, resistant, antibiotic